Studies of gain and lasing in thulium doped fibres - Tessarin, Severino (Trinity College (Dublin, Ireland). School of Physics, 2006)
Rare earth ions have absorption and emission lines in almost the entire transparent region of silica optical fibres, and they can be used as dopants inside the fibre core of single mode optical fibres employed for telecommunication. Erbium amplifiers has been far more successful than any other rare-earth doped amplifiers due to their unique properties such as high gain, low noise, polarization insensitivity and broad spectral bandwidth and they operate at 1550 nm- the wavelength where standard silica fibres have minimum losses.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin